Cortical Development and Brain Malformations: Insights From the Differential Regulation of Early Events of DNA Replication - Kalogeropoulou, Argyro; Lygerou, Zoi; Taraviras, Stavros (Frontiers in Cell and Developmental Biology, 2019)
During the development of the cortex distinct populations of Neural Stem Cells (NSCs) are defined by differences in their cell cycle duration, self-renewal capacity and transcriptional profile. A key difference across the distinct populations of NSCs is the length of G1 phase, where the licensing of the DNA replication origins takes place by the assembly of a pre-replicative complex. Licensing of DNA replication is a process that is adapted accordingly to the cell cycle length of NSCs to secure the timed duplication of the genome. Moreover, DNA replication should be efficiently coordinated with ongoing transcription for the prevention of conflicts that would impede the progression of both processes, compromising the normal course of development. In the present review we discuss how the differential regulation of the licensing and initiation of DNA replication in different cortical NSCs populations is integrated with the properties of these stem cells populations. Moreover, we examine the implication of the initial steps of DNA replication in the pathogenetic mechanisms of neurodevelopmental defects and Zika virus-related microcephaly, highlighting the significance of the differential regulation of DNA replication during brain development.